Hydrothermal alteration processes in monzogranite: a case study from the Eastern Desert of Egypt: implications from remote sensing, geochemistry and mineralogy - Amira M. El Tohamy (Geochemical Transactions, 2024)
Abstract The South Eastern Desert (SED) of Egypt is one of the most promising areas in Egypt; it is widely explored for exploring the rare earth elements (REEs) and uranium-bearing ores. It is a main part of the Arabian-Nubian Shield (ANS). Therefore, the present study concerns with Sikait-Nugrus area as one of the most prolific sites in this region. The study provides a detailed geological, structural, and mineralogical investigation of the monzogranites to describe and characterize the various alteration types and sequence. For this purpose, remote sensing, geochemical and petrographical techniques were applied. The remote sensing technique helped in constructing a detailed geologic map of the study area to follow up strictly the alteration zone of the Sikait-Nugrus area. Petrographically, the granites predominates in the study area, they are described as slightly and highly altered monzogranites. The slightly altered one is composed mainly of quartz (~ 20–35%), alkali feldspar (~ 25–30%), plagioclase (~ 25–30%), and mica (~ 5–15%), while accessory minerals are represented by zircon and monazite. On the other hand, the portion of this granite close to the shearing zone is intensively altered and characterized by sericitization as the main alteration processes. This sheared portion is characterized by accessory minerals as, uranothorite, allanite, fluorite and Nb-minerals (ishikawaite). Minerlogically, the altered monzogranites are predominated by the following mineral groups: (1) radioactive minerals as uranyl silicates (soddyite, uranophane and kasolite), and thorium minerals (thorite and uranothorite), (2) Nb–Ta minerals (betafite, plumbobetafite, columbite, fergusonite, and aeschynite), (3) REE minerals (monazite, cheralite and xenotime), and (4) zircon and fluorite as accessory minerals. Geochemically, the recorded pattern of the REEs tetrad effect (M-type) for the highly altered samples indicate that these granites are highly evolved and affected by late stage of hydrothermal alteration and the effective water-rich alteration processes that connected to intensive physico-chemical changes. The total REE concentrations equal 241.8 and 249.75 ppm for the highly and slightly altered samples. A significant mass change (MC) was analyzed by the isocon technique (22.95 & 11.11) and volume change (VC) (1.8 &-7.99) for the highly and slightly altered samples, respectively. The mass balance calculations and the isocon diagrams revealed that some major oxides were removed from the slightly altered monzogranites and transformed later into highly altered monzogranites with increasing the alteration intensity due to the impacts of hydrothermal alteration processes. The studied area is virgin, where no detailed studies have been applied to this region. It is extendable to other parts of the Arabian-Nubian Shield in around the Red Sea in Egypt, Sudan, Saudi Arabia and Yemen. The applied technical workflow is also extendible to other surface analogues everywhere.